Efforts to Improve Education to Protect Children from Sexual Violence - Fidiyani, Rini; Kamal, Ubaidillah; Ningsih, Ayup Suran; Prasetyo, Kresna Adi; Lestari, Lilis Eka (Universitas Negeri Semarang, 2025)
The phenomenon of child victims of sexual violence increased during COVID-19 from 2021 to 2022. This indicates that COVID-19 is a vulnerable and dangerous situation because children live near their families and interact with social environments outside of school. Child victims of sexual violence are often difficult to obtain information about the legal incidents that befell them. This is due to the limited vocabulary of children and their vulnerability to threats from perpetrators, which can result in psychological trauma for the victims. The objectives of this community service program are: first, to map the types of violence affecting child victims; second, to prevent and address child victims of sexual violence. The community service methods used include: a pre survey of the locations and situations that will be the target of community service; second, observation and interviews with neighborhood and local residents' association officials who include young families with children; and third, offline community service and discussions with young families with children. The results obtained include a diversity of types of violence against child victims, and, fundamentally, children's mental and physical development can be affected in the future. Efforts to prevent and handle child victims of sexual violence require obtaining statements from child victims in a language that children understand and involving parties who are trusted and competent in addressing the basic needs of child victims of sexual violence.